MENEMUKAN KEARIFAN LINGKUNGAN DALAM POLA PEMUKIMAN KERATON BUTON - Muhammad Nur; Rustam Awat (WalennaE, 2010)
Keraton Buton (the palace of Buton Kingdom) has a settlement pattern which was depicting the spatial arrangement and a function of a complex spatial. The equilibrium of settlement pattern of Keraton Buton has been charged to the Siolimbona, a local custom institution for the last 4 centuries. Since I960, the Siolimbone were removed and as the result a settlement disorder raised. Environmental wisdom of the custom institution of Siolimbona was proved have more effectiveness compared with local act of present regional government of Buton.Keraton Buton (istana Kerajaan Buton) memiliki pola pemukiman yang menggambarkan tata ruang dan fungsi tata ruang yang kompleks. Keseimbangan pola pemukiman Keraton Buton telah dibebankan ke Siolimbona, sebuah lembaga adat setempat selama 4 abad terakhir. Sejak tahun 1960, Siolimbone telah dihapus dan sebagai hasilnya gangguan pemukiman meningkat. Kearifan lingkungan lembaga adat Siolimbona terbukti lebih efektif dibandingkan dengan tindakan lokal pemerintah daerah Buton saat ini.